Characteristics of Mechanical Outputs During Rowing Motion: Comparison Between Fixed and Slide Rowing Ergometers - Hyunchul Yoon; Natsumi Furuta; Kazuo Funato (The Asian Journal of Kinesiology)
OBJECTIVES This study compared the mechanical outputs and lower joint kinematics during rowing motion using fixed and slide-type rowing ergometers to clarify the slide type's characteristics. METHODS Junior rowers performed a simulated 2000m race pace under two ergometer conditions. Rowing motion was filmed by a high-speed video camera (200 fps) from right angles beside the subject and changes in Hip and knee joint angles were measured. Spatiotemporal parameters as well as force output from the handle and stretcher and joint angle kinematics at 500m spot calculated. RESULTS In the 2000m time trial, the two conditions showed no significant difference. However, significant differences were observed in the maximum stretcher force, with the slide-type rowing ergometer showing higher values than the fixed-type rowing ergometer. On the other hand, greater values in handle force were found for the fixed-type rowing ergometer than slide-type rowing ergometer greater. Greater rate of force development for the handle and stretcher were observed in the slide-type rowing ergometer condition. No significant differences were observed in angular changes between the two conditions, but knee and hip maximum angular accelerations were significantly higher in the slide-type rowing ergometer condition. Higher stretcher force in slide-type rowing ergometer at the beginning of the stroke is characterized as the influence of maximal angular acceleration in both knee and hip joint extensions, causing high rate of force development of handle and stretcher forces in the initial phase of the drive. As a result, the muscle groups including the biarticular muscles around hip and knee joints may work in coordination to exert significant force, a defining characteristic of the slide-type rowing ergometer. CONCLUSIONS The fix-type rowing can be used effectively to strengthen the maximum handle pull strength, mainly upper extremity. On the other hand, slide-type rowing can be used effectively to strengthen the maximum stretcher force as well as it’s rate of force development, which might be similar force output of lower extremity as performed during on-water rowing.